The dire need for a portal on halal matters: a one-stop source of information on the concept of halal? - Syed Azamthullah, Syed Salim Agha (TM-Info-Media Sdn. Bhd., 2009)
One possible reason why non-Muslims, in particular, do not understand various Islamic teachings and concepts is the failure of Muslims to explain in a clear and concise manner the meaning and significance of Islamic teachings,concepts or principles that are put across. Explanations using language which is simple and easily understood will help to develop a greater understanding of Islam, its practice and culture.